Identifying genomic variant associated with long QT syndrome type 2 in an ecuadorian mestizo individual: a case report - Tamayo-Trujillo, Rafael; Ibarra-Castillo, Rita; Laso-Bayas, José Luis; Guevara-Ramirez, Patricia; Cadena-Ullauri, Santiago; Paz-Cruz, Elius; Ruiz-Pozo, Viviana A.; Doménech, Nieves; Ibarra-Rodríguez, Adriana Alexandra; Zambrano, Ana Karina (Frontiers in Genetics, 2024)
Introduction: Long QT syndrome (LQTS) is an autosomal dominant inherited cardiac condition characterized by a QT interval prolongation and risk of sudden death. There are 17 subtypes of this syndrome associated with genetic variants in 11 genes. The second most common is type 2, caused by a mutation in the KCNH2 gene, which is part of the potassium channel and influences the final repolarization of the ventricular action potential. This case report presents an Ecuadorian teen with congenital Long QT Syndrome type 2 (OMIM ID: 613688), from a family without cardiac diseases or sudden cardiac death backgrounds. Case presentation: A 14-yearold girl with syncope, normal echocardiogram, and an irregular electrocardiogram was diagnosed with LQTS. Moreover, by performing Next-Generation Sequencing, a pathogenic variant in the KCNH2 gene p.(Ala614Val) (ClinVar ID: VCV000029777.14) associated with LQTS type 2 , and two variants of uncertain significance in the AKAP9 p.(Arg1654GlyfsTer23) (rs779447911), and TTN p.(Arg34653Cys) (ClinVar ID:VCV001475968.4) genes were identified. Furthermore, ancestry analysis showed a mainly Native American proportion. Conclusions: Based on the genomic results, the patient was identified to have a high-risk profile, and an implantable cardioverter defibrillator was selected as the best treatment option, highlighting the importance of including both the clinical and genomics aspects for an integral diagnosis.